Hubungan Pola Asuh Demokratis dan Interaksi Teman Sebaya dengan Kecerdasan Emosional Siswa Kelas V Madrasah Ibtidaiyah Negeri 1 Bebesen - Atika Sabaria R; Abdul Munir; Cut Metia (Universitas Medan Area, 2019)
This research aims to determine the relationship between democratic parenting and peer interaction with emotional intelligence. The hypothesis proposed, there is a positive relationship between democratic parenting and peer interaction with emotional intelligence, the higher democratic parenting pattern and peer interaction, so the emotional intelligence will be the higher also . The population in this research amounted to 113 people and the sample in this research amounted to 85 people. The method that researchers use is quantitative and for take a sampling technique researchers using total sampling technique. Scale form in the researchers using Guttman scale with the coefficient of reliability in democratic parenting of 0.903 on peer interaction of 0.764 and on emotional intelligence of 0.888. Data analysis that researchers used is multiple regression analysis and partial correlation. Based on the result, researchers concluded that there is a significant relationship between democratic parenting and peer interaction with emotional intelligence, as shown by coefficient r = 0.518; with p = 0.00 means (p 0.01) it’s means that the higher the democratic parenting pattern and peer interaction so the emotional intelligence will be the higher also . Based on the empirical mean and hypothetical variables mean of democratic parenting in this research is (70.106 57.00), Interaction variables of peers (44.047 36.00), and emotional intelligence variables (64.176 52.500) known that the subject of research has a democratic parenting, interaction peers and high emotional intelligence.